Effectiveness of Methanol Extract Combination of Cymbopogon citratus stem and Syzygium aromaticum L. leaf as a Larvacide Against Aedes aegypti - Bunga Enjlin Natasya; Tri Wulandari Kesetyaningsih (CV. Inara, 2026)
Dengue Hemorrhagic Fever (DHF) is a common disease in tropical countries, including Indonesia. The control of Ae. aegypti vectors relies on chemical insecticides, which can cause resistance and environmental pollution. Therefore, the use of biolarvicides is considered a safer alternative. Lemongrass (Cymbopogon citratus) stems and clove (Syzygium aromaticum L.) leaves are known to contain active compounds with larvicidal potential. This study aimed to determine the effectiveness of a 1:1 methanolic extract combination of lemongrass (Cymbopogon citratus) stems and clove (Syzygium aromaticum L.) leaves as a larvicide against Ae. aegypti based on different concentration levels. The study used an experimental method with a longitudinal prospective design. Seven treatment concentrations (0,5%; 0,75%; 1,5%; 3%; 5%; 7%; and 10%) were tested on Ae. aegypti third-instar larvae with four replications. Larval mortality was observed every hour for 12 hours, and probit analysis was used to determine LC50, LC90, LT50, and LT90 values. Larval mortality increased linearly with higher extract concentrations. The LC50 value was 0,0385%, and the LC90 value was 7,885%. At the lowest concentration (0,5%) the LT50 and LT90 values were 3,292 hours and 6,970 hours, respectively, while at the highest concentration (10%), both values <1 hours. There was a linear relationship between the concentration of the tested extract and larval mortality. The 1:1 methanolic extract combination of lemongrass stems and clove leaves proved effective as a biolarvicide against Ae. aegypti as indicated by the LC50, LC90, LT50, and LT90 values.